2006
DOI: 10.1107/s0907444906030587
|View full text |Cite
|
Sign up to set email alerts
|

Automation of sample mounting for macromolecular crystallography

Abstract: A standard sample holder and vial for cryocooled macromolecular crystals has been defined for use with robotic sample changers. This SPINE standard sample holder is a modified version, with added features and specifications, of sample holders in common use. In particular, the SPINE standard meets the precision required for automatic sample exchange and includes a cap that is identified by a two-dimensional datamatrix code as well as an optional vial. At the ESRF, the sample holder standard is in use with the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
114
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 11 publications
0
114
0
Order By: Relevance
“…The combination of highly intense focused X-ray beams, automatic sample changers, automated beam delivery, online data analysis and fast readout detectors at synchrotron macromolecular crystallography (MX) beamlines now allows for the collection of hundreds of datasets during each assigned experimental session (Arzt et al, 2005;Beteva et al, 2006;Bourenkov & Popov, 2010;Bowler et al, 2010;Cherezov et al, 2009;Cipriani et al, 2006;de Sanctis et al, 2012;Flot et al, 2010;Gabadinho et al, 2010;Incardona et al, 2009;Jacquamet et al, 2009;Leslie et al, 2002;McCarthy et al, 2009;McPhillips et al, 2002;Nurizzo et al, 2006;Soltis et al, 2008). In many cases, complete diffraction datasets can be collected in under one minute (Hü lsen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of highly intense focused X-ray beams, automatic sample changers, automated beam delivery, online data analysis and fast readout detectors at synchrotron macromolecular crystallography (MX) beamlines now allows for the collection of hundreds of datasets during each assigned experimental session (Arzt et al, 2005;Beteva et al, 2006;Bourenkov & Popov, 2010;Bowler et al, 2010;Cherezov et al, 2009;Cipriani et al, 2006;de Sanctis et al, 2012;Flot et al, 2010;Gabadinho et al, 2010;Incardona et al, 2009;Jacquamet et al, 2009;Leslie et al, 2002;McCarthy et al, 2009;McPhillips et al, 2002;Nurizzo et al, 2006;Soltis et al, 2008). In many cases, complete diffraction datasets can be collected in under one minute (Hü lsen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The initial online set-up was used from 2003 to 2005 [for example, in research reported by Dubnovitsky et al (2005)] and had a large working distance (lens to sample = 50 mm), allowing easy access to the goniometer for manual mounting and dismounting of the crystal. With the wide-scale automation of the ESRF MX beamlines (Arzt et al, 2005;Beteva et al, 2006;Cipriani et al, 2006), a second-generation sample-changercompatible online microspectrophotometer was designed [used, for example, by Macedo et al (2009)], based on smaller lenses and a smaller working distance (lens to sample = 35 mm). Details of the design as well as plans for future generations of online microspectrophotometers are given in x2.…”
Section: Introductionmentioning
confidence: 99%
“…Just like screening and optimization, accurate recording of this information on a large scale may well be able to inform choice of strategy for individual cases. This pipelining between crystallization and (automated) data collection has been addressed by collaborative work between SPINE, the e-HTPX project, synchrotrons and others to produce systems such as DNA (automated collection of data) and ISPyB (information system for protein crystallography beamlines) that exploit recent developments in automated beamline sample changers (see Beteva et al, 2006;Cipriani et al, 2006). Test pipelines are now in place, with one immediate benefit being the ability to view diffraction images remotely over the web as JPEG thumbnails and full-size images within a few seconds of collection.…”
Section: Links To Downstream Activitiesmentioning
confidence: 99%